Silk fibroin nanoparticles for enhanced bio-macromolecule delivery to the retina. (28th May 2019) - Yang, Pianpian; Dong, Yixuan; Huang, Di; Zhu, Chune; Liu, Hu; Pan, Xin; Wu, Chuanbin
Abstract: The aim of this study was to investigate intravitreal injection of silk fibroin nanoparticles (SFNs) encapsulating bio-macromolecules, achieving enhanced drug bioavailability, and extended retention in retina. SFNs were prepared with regenerated silk fibroin using desolvation method with fluorescein isothiocyanate labeled bovine serum albumin (FITC-BSA) as bio-macromolecular model drug encapsulated. In vitro physicochemical properties and in vitro drug release of FITC-BSA loaded SFNs (FITC-BSA-SFNs) were evaluated. Cytotoxicity, cellular uptake, and retention of FITC-BSA-SFNs were determined in human retinal pigment epithelial cell line (ARPE-19). In addition, in vivo distribution and safety of intravitreally administered FITC-BSA-SFNs were investigated in New Zealand white rabbits. The particle size of FITC-BSA-SFNs was 179.1 ± 3.7 nm with polydispersity index of 0.102 ± 0.033 and the zeta potential was greater than −25 mV. FITC-BSA-SFNs exhibited excellent biocompatibility with no cytotoxicity observed within 24 and 48 h in AREP-19 cells. Compared to FITC-BSA solution, FITC-BSA-SFNs showed enhanced cellular uptake and prolonged retention. Furthermore, FITC-BSA-SFNs achieved accumulated distribution and extended retention in retina in vivo following intravitreal injection compared to a single administration of free drug solution. Therefore, this bio-macromolecule delivery platform based on SFNs could have great potential in the treatment of posterior segment disorders.